PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK KELAS III MI NURUL HUDA AS-SURIAH BOJONGSARI - Diah Kurnia Rahayu (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2022)
Based on problem of the low participation af learners, the authors do research on the Use of Active Learning Strategy Type Everyone Is A Teacher Here to Increase Student Learning Participation in Thematic Learning of Class III MI Nurul Huda As-Suriah Bojongsari. The study aims to increase the learning participation of learners using the active learning strategy type Everyone Is A Teacher Here on thematic lesson class III MI Nurul Huda As-Suriah Bojongsari. The research method used is Classroom Action Research method which implemented two cycles. The subject of the research is the students of the III grade of MI Nurul Huda As-Surih Bojongsari. Data collection techniques used are observation, interview and documentation. The data analysis was done on descriptively qualitative. The result of cycle I and cycle II there is a percentage increase of 14% of student that’s is in the cycle I 77% of students to 91% of student in cyle II with very good category.